Child sexual abuse and sleep disturbances among adolescents: the role of post-traumatic stress disorder symptoms - Hébert, Martine; Théorêt, Valérie; Tremblay-Perreault, Amélie; Zadra, Antonio (Frontiers in Psychology, 2025)
IntroductionSleep disturbances represent a major concern for many adolescents. While adolescents with a history of trauma may be particularly vulnerable to sleep disturbances, the mechanisms underlying the association between childhood sexual abuse and sleep disturbances (e.g., having trouble falling asleep, nightmares) remain understudied. The present study aimed to: (1) explore sleep disturbances among adolescents with a history of childhood sexual abuse, and (2) investigate the mediating role of PTSD symptoms in the association between childhood sexual abuse and sleep disturbances.MethodsData were drawn from a representative sample of 8,194 adolescents in grades 9 to 11. The history of childhood sexual abuse and PTSD symptoms were assessed at Time 1, whereas sleep disturbances were assessed 6 months later (Time 2) using self-reported questionnaires.ResultsAdolescents who experienced childhood sexual abuse were more likely to report sleep disturbances than those who experienced other forms of childhood adversity. Sexual abuse was associated with higher levels of PTSD symptoms at Time 1, which, in turn, predicted more sleep disturbances at Time 2.DiscussionThese findings suggest that sleep disturbances should be monitored and addressed in trauma-focused therapy for youth victims of childhood sexual abuse.